If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10p + -6 = -4 + 6p Reorder the terms: -6 + 10p = -4 + 6p Solving -6 + 10p = -4 + 6p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-6p' to each side of the equation. -6 + 10p + -6p = -4 + 6p + -6p Combine like terms: 10p + -6p = 4p -6 + 4p = -4 + 6p + -6p Combine like terms: 6p + -6p = 0 -6 + 4p = -4 + 0 -6 + 4p = -4 Add '6' to each side of the equation. -6 + 6 + 4p = -4 + 6 Combine like terms: -6 + 6 = 0 0 + 4p = -4 + 6 4p = -4 + 6 Combine like terms: -4 + 6 = 2 4p = 2 Divide each side by '4'. p = 0.5 Simplifying p = 0.5
| 7h+7h= | | 61-4x=41x+15 | | 7-7x=29-14x | | 3(2p+7)=24 | | 6x+9=17-7x | | 128-3x=6x+12 | | 2(5*6)= | | 5[t-1]=20 | | x=30-y | | 28=2(2w+5)+2w | | 7x-21=63 | | 96=2(2w)+2w | | 19000+n-1200=35000 | | -9x+2.2=-3x+7 | | (8x-7)-4=3x | | 13+4x=-43-10x | | x-7=8x | | 59+55*n=224 | | 43-2x=7x+22 | | y+4=8x-7 | | X*X+37=14X-8 | | l+9w=460 | | 11x-40+5x+2= | | n+10*4=22 | | 3x=(3x+4)*8x | | -6(x-6)=3(x+0) | | 3x=(3x+4)*8 | | 2x+1100=50800 | | 15x+26(x-4)=511 | | 12x+96=-3x+141 | | (0.5-x)(0.5-x)=4 | | 3n+6=21 |